An Analysis of the Islamic Religious Education Curriculum at SMA Muhammadiyah 2 Bandar Lampung - Istiana, Laisa; Syafe’i, Imam; Isti’ana, Ais; Wahyudi, Waluyo Erry; Bahri, Saiful (International Journal on Advanced Science, Education, and Religion, 2024)
By combining the Merdeka Curriculum with the unique Muhammadiyah curriculum, this research attempts to examine the PAI curriculum at SMA Muhammadiyah 2 Bandar Lampung. The main focus of this research is on the curriculum development process and the results of its implementation, which combines the unique ideals of Muhammadiyah Islam with the adaptability and creativity exemplified by the Merdeka Curriculum. Field research methods were used in conjunction with a qualitative descriptive approach. In-depth interviews, observations, and document analysis were used to collect information. Eleventh grade students, curriculum administrators, and Islamic Religious Education teachers at SMA Muhammadiyah 2 Bandar Lampung were the subjects of the research. The results of the research showed that the development of Islamic personality, religious description, and 21st century skills of students were successfully strengthened through this curriculum integration. Through continuous training and increased cooperation between schools and Muhammadiyah organizations, problems including limited human resources and teacher competence were overcome. This study supports Muhammadiyah's learning objectives to produce a generation of people who are religious, pious, and have global capabilities, while also participating in and producing a religion-based curriculum that is relevant to the demands of the era.